Escherichia coli bloodstream infection outcomes and preventability: a six-month prospective observational study. Issue 2 (October 2019) - Lillie, P.J.; Johnson, G.; Ivan, M.; Barlow, G.D.; Moss, P.J.
Abstract: Background: Escherichia coli bloodstream infection (BSI) is a common and serious problem, and incidence and antibiotic resistance are increasing. Aim: To understand the drivers of outcomes and factors associated with preventable cases at the study institution. Methods: Between 1 st November 2017 and 30 th April 2018, cases of E. coli BSI in adults treated as inpatients at the study institution were included in a prospective cohort. Clinical, demographic and laboratory features were recorded, with seven-, 30- and 90-day mortality and length of hospital stay post BSI. Qualitative data on preventability were reviewed independently by two infection specialists. Findings: In total, 195 cases in 188 patients were included in the analysis. Empirical antibiotics showed in-vitro resistance in 30.9% of cases. Thirty-day mortality was 23.6%, with a median length of hospital stay of seven days. On multi-variable analysis, 30-day mortality was associated with higher Charlson score, residential home residency, higher respiratory rate and higher serum urea, whilst prolonged length of stay was associated with hospital-acquired E. coli BSI. Fifty patients were felt to have avoidable BSI, all of which were health care associated; urinary catheter use, antibiotic-related and procedural complications were the areas of preventability. Conclusions: E. coli BSI has an appreciable mortality, with little in the way of modifiable risk factors for mortality or prolonged hospital stay. Attention to urinary catheter use is likely to be the most useful way to reduce the incidence, but current UK reduction targets may be unachievable.